2019
DOI: 10.1002/ente.201900022
|View full text |Cite
|
Sign up to set email alerts
|

Highly Reversible Phase Transition Endows V6O13 with Enhanced Performance as Aqueous Zinc‐Ion Battery Cathode

Abstract: Aqueous zinc‐ion batteries (ZIBs), with favorable merits of high security and low cost, have gained much interest in the energy storage field. However, their development is still in its infancy. Herein, V6O13 is investigated as aqueous ZIB cathodes with excellent Zn2+ storage performance, as compared with VO2 and V2O5. The intrinsic open structure of V6O13 with mixed‐valance states of vanadium (V4+/V5+) is favorable to enable fast Zn2+ ion diffusion and improved electronic conductivity, outperforming VO2 and V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 127 publications
(77 citation statements)
references
References 58 publications
(105 reference statements)
1
68
0
Order By: Relevance
“…To further compare the difference of the zinc foils by electrowinning with or without mixed additives, galvanostatic charge/discharge was conducted between 1.4 and 2.1 V at 4 C-rate. As shown in Figure 5(a), there are two distinguished plateaus using the electrowinning zinc adding TU and GL that reflect two-stage Li-ion extraction/insertion behavior and are consistent with the previous reports [27]. In Figure 5(b), the capacity retentions after 300 cycles are 1.62%, 34.88%, and 45.63%, respectively, for three parallel batteries, of which the zinc current collectors were cut from the same piece of zinc foil by electrowinning from a sulfate solution containing 58 g/L Zn 2+ and 150 g/L H 2 SO 4 without additives in the electrolyte, and the consistency of the zinc is very bad.…”
Section: The Electrochemical Performance Of Battery Withsupporting
confidence: 91%
See 1 more Smart Citation
“…To further compare the difference of the zinc foils by electrowinning with or without mixed additives, galvanostatic charge/discharge was conducted between 1.4 and 2.1 V at 4 C-rate. As shown in Figure 5(a), there are two distinguished plateaus using the electrowinning zinc adding TU and GL that reflect two-stage Li-ion extraction/insertion behavior and are consistent with the previous reports [27]. In Figure 5(b), the capacity retentions after 300 cycles are 1.62%, 34.88%, and 45.63%, respectively, for three parallel batteries, of which the zinc current collectors were cut from the same piece of zinc foil by electrowinning from a sulfate solution containing 58 g/L Zn 2+ and 150 g/L H 2 SO 4 without additives in the electrolyte, and the consistency of the zinc is very bad.…”
Section: The Electrochemical Performance Of Battery Withsupporting
confidence: 91%
“…Based on the defects and limitations of aqueous rechargeable lithium ion batteries (ARLIBs), a hybrid cationic aqueousbased rechargeable battery system based on lithium intercalation cathode with undoped LiMn 2 O 4 and low equilibrium potential and low-cost zinc anode was first reported by Chen's group [19]. Since then, they have attracted increasing concerns about aqueous batteries [20,21] and the similar systems such as Na 0.44 MnO 2 //Zn [22], LiMnPO 4 //Zn [23], LiCo 1/3 Mn 1/3 Ni 1/3 PO 4 //Zn [24], and so on [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the introduction of metal ions enables the vanadium-oxide layers transformed into VO 5 square pyramidals and VO 6 octahedras, thus leading to the c-axis extension, which synergistically constructed a more stable bilayered V 3 O 8 structure along the b-axis, demonstrating higher stability than the structure only containing VO 5 square pyramidals during charging/discharging process. [176][177][178] Besides, to explore the influence of metal ions on the transport kinetics, GITT measurement was carried out to calculate the corresponding Zn 2+ diffusivity coefficient (D). As displayed in Figure 6b, the calculated D results showed that all the preintercalated V 2 O 5 samples exhibit about one order of magnitude higher than that of the pristine one.…”
Section: Ions Intercalationmentioning
confidence: 99%
“…On the one hand, the V 5+/4+ redox pair could provide high specific capacity. On the other hand, the unique electronic characteristics endow them with considerable pseudocapacitance behaviour especially in aqueous systems (such as more than 400 mAh g −1 of V 6 O 13 in AZIBs) [7] . Furthermore, most vanadium‐based oxides, including the VO 2 , [8,9] V 2 O 5 , [10] V 3 O 7 , [11] MV 2 O 6 , [12] M 3 V 2 O 8 , [13] etc.…”
Section: Introductionmentioning
confidence: 99%